2001
DOI: 10.5144/0256-4947.2001.183
|View full text |Cite
|
Sign up to set email alerts
|

Obesity among Adult Bahraini Population: Impact of Physical Activity and Educational Level

Abstract: Background:In the populations of the Arabian Peninsula, obesity has emerged as the leading cause of morbidity and mortality over a 25-year period of swift socioeconomic progress. The objective of this study was to determine the body weight distribution, prevalence and risk factors for the overweight and obese in the native adult Bahraini population. Subjects and Methods A cross-sectional national epidemiological community survey was conducted involving 2013 Bahraini subjects aged 40-69. The males were aged 40-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 20 publications
3
43
2
Order By: Relevance
“…The prevalence in this study is higher as compared to various previous studies (9)(10)(11)(12)(13)(14) done on general population groups. These studies showed a prevalence ranging from 7% to 34%.…”
Section: Discussioncontrasting
confidence: 76%
“…The prevalence in this study is higher as compared to various previous studies (9)(10)(11)(12)(13)(14) done on general population groups. These studies showed a prevalence ranging from 7% to 34%.…”
Section: Discussioncontrasting
confidence: 76%
“…Furthermore, WHO reports have identified obesity as the most pressing health concern in the MENA region and recent studies indicate that, as elsewhere in the developed world, the prevalence of obesity is likely to rise in the years ahead [41] . Whereas obesity initially affected the higher socioeconomic strata of the population, current evidence also suggests a shift in obesity prevalence to the lower socioeconomic groups [51] . Although a disease in itself, obesity is considered an underlying and modifiable risk factor for CVD.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Social factors make it unacceptable for women to walk or exercise alone outside the house without the company of a family member. Furthermore, a culture that promotes 'plumpness' as a sign of beauty, health and affluence has been suggested as an underlying factor for the high prevalence of obesity in the affluent countries [41,51,58,59] . Eating habits (dish sharing) and types of clothing (abaya or wide gowns) worn by a substantial proportion of the women in the Arab countries are additional factors that may significantly contribute to the rise in obesity levels [16] .…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Abbas et al (2003) 22 reported a prevalence of 7% obesity in their study . 26 reported, the prevalence of obesity was significantly higher among female subjects than males in all the age groups. Overweight and obesity were more prevalent among those with high incomes.…”
Section: Discussionmentioning
confidence: 77%